2008
DOI: 10.1631/jzus.b0820058
|View full text |Cite
|
Sign up to set email alerts
|

MGB probe assay for rapid detection of mtDNA11778 mutation in the Chinese LHON patients by real-time PCR

Abstract: Abstract:Objective: Leber's hereditary optic neuropathy (LHON) is a maternally inherited degeneration of the optic nerve caused by point mutations of mitochondrial DNA (mtDNA). Many unsolved questions regarding the penetrance and pathophysiological mechanism of LHON demand efficient and reliable mutation testing. This study aims to develop a minor groove binder (MGB) probe assay for rapid detection of mtDNA11778 mutation and heteroplasmy in Chinese LHON patients by real-time polymerase chain reaction (PCR). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
7
0
4
Order By: Relevance
“…The mitochondrial genome has been assessed employing a variety of different strategies [Wang et al, 2008a;Wong and Bai, 2006;Wong and Senadheera, 1997]. In this study, fragments from the mtDNA scanning panel identified heteroplasmic variants ranging from 1 to 100% mutant allele fraction (Table 1; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial genome has been assessed employing a variety of different strategies [Wang et al, 2008a;Wong and Bai, 2006;Wong and Senadheera, 1997]. In this study, fragments from the mtDNA scanning panel identified heteroplasmic variants ranging from 1 to 100% mutant allele fraction (Table 1; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of specific variants has been performed by allele-specific PCR, a variety of real-time PCR procedures, and real-time amplification refractory mutation system quantitative PCR [Wang et al, 2008a;Wong and Bai, 2006;Wong and Senadheera, 1997]. Mitochondrial DNA sequence variants have been screened for by indirect means such as denaturing high-performance liquid chromatography, denaturing gradient gel electrophoresis, temperature gradient gel electrophoresis, and other methods [van Den Bosch et al, 2000;van Eijsden et al, 2006;White et al, 2005;Wong et al, 2004Wong et al, , 2002Xiu-Cheng Fan et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Nhi u nghi n ứu ho r ng d ng kh ng đồng nhất ủ đột biến ó thể ảnh hưởng một phần đến s biểu hi n v di truy n ủ b nh LHON [9][10]. V v y vi xá định á nhân t góp phần l m th y đ i kiểu h nh ủ đột biến v những hiểu biết v ơ hế phát sinh b nh do đột biến G11778A l ần thiết.…”
Section: Mở đầU unclassified
“…Current diagnostic strategies for the 3 most common mutations causing LHON include individual endpoint PCR-RFLP [ 29 ], allele specific PCR [ 30 ], real time PCR [ 31 ] and PCR followed by Sanger / pyrosequencing [ 32 ]. In this study, we successfully designed a simple multiplex PCR-RFLP to detect the 3 primary mitochondrial LHON mutations and also describe the synthesis of a series of LHON control sequences that act as a robust and patient-free resource for LHON test controls and assay development.…”
Section: Introductionmentioning
confidence: 99%